2020
DOI: 10.1111/1346-8138.15553
|View full text |Cite
|
Sign up to set email alerts
|

Moderation analysis exploring associations between age and mucocutaneous activity in Behçet’s syndrome: A multicenter study from Turkey

Abstract: The aim of the present study was to examine the effects of age on mucocutaneous activity by using moderation analysis in Behc ßet's syndrome (BS). In this cross-sectional study, 887 BS patients (female : male, 481:406; mean age, 38.4 AE 10.9 years) followed in 13 tertiary centers in Turkey were included. Mucocutaneous activity was evaluated by using the Mucocutaneous Index (MI) according to sex and disease course. Moderation analysis was performed to test the effect of age on mucocutaneous activity. A moderato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Most of the patients with BS had active oral ulcers and negative self-reported Treatment Response. Oral ulcer activity is commonly seen in mucocutaneous involvement and also thought to be risk factor for more severe disease course ( 2 , 19 , 20 ). Since oral ulcers lead to pain and functional limitation ( 21 , 22 ), patient’s life is poorly affected by them in BS ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients with BS had active oral ulcers and negative self-reported Treatment Response. Oral ulcer activity is commonly seen in mucocutaneous involvement and also thought to be risk factor for more severe disease course ( 2 , 19 , 20 ). Since oral ulcers lead to pain and functional limitation ( 21 , 22 ), patient’s life is poorly affected by them in BS ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the study was to show key points for Daily activity impairment by using both mediation and moderation analyses in patients with pSS. These analyses helped to understand hidden relations on outcome variables in clinical practice (Mumcu et al, 2020; Yay et al, 2019). In previous studies, increase in oral ulcer‐related pain in Behcet's disease (Karacayli et al, 2021) and HADS‐D score in Takayasu arteritis (Erdal et al, 2021) are found to be significant mediators for WPAI‐Daily activity impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a moderator variable (W) is defined as a third variable affecting the direction of the relationship between the dependent (Y) and independent variable (X) (Hayes, 2018; Hayes & Rockwood, 2017). In our previous studies, these analyses are used to understand associations among symptoms in Behcet's disease (BS) (Karacayli et al, 2021; Mumcu et al, 2020; Yay et al, 2019) and Takayasu arteritis (TAK) (Erdal et al, 2021). The aim of this cross‐sectional study was to show relations between activity impairment and salivary gland involvement for patient empowerment in patients with primary Sjogren's syndrome (pSS).…”
Section: Introductionmentioning
confidence: 99%
“…Oral ulcer activity may run in parallel with musculoskeletal [30] and genital ulcer activity [37], as well as with psycho-social well-being [33], all of them affecting the functionality and quality of life [30]. Moreover, increased mucocutaneous activity, as the activity of oral ulcers, may be associated with new major organ involvement in young female BD patients with systemic involvement [39]. It is worth mentioning that oral ulcers may have role in triggering systemic activation, because oral microorganisms and inflammatory mediators could gain access to systemic circulation through the disruption of the mucosal barrier [36,40,41].…”
Section: Disease Activitymentioning
confidence: 99%